2017
DOI: 10.1017/s0022215117000561
|View full text |Cite
|
Sign up to set email alerts
|

Importance of a dedicated neuroradiologist in reporting high-resolution computed tomography for otosclerosis: a retrospective comparison study of 40 patients

Abstract: The use of high-resolution computed tomography for suspected otosclerosis is helpful for diagnosis, disease staging, obtaining informed consent, surgical planning and prognosis. This study suggests that radiological detection of otosclerotic changes by high-resolution computed tomography of the temporal bone is significantly better when performed by a dedicated neuroradiologist than by a general radiologist. Use of a standardised temporal bone computed tomography protocol is recommended to provide consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 9 publications
3
15
0
1
Order By: Relevance
“…In their study, the neuroradiologist arrived at the diagnosis in 100% of cases, the general radiologists in 10%, a statistically significant difference. 10 Our comparison of local radiologists with our collaborating neuroradiologist is more heterogeneous as some locally obtained studies may have been read by a neuroradiologist. While the local radiologists were likely mostly general radiologists, this information was not evaluated based on the study design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study, the neuroradiologist arrived at the diagnosis in 100% of cases, the general radiologists in 10%, a statistically significant difference. 10 Our comparison of local radiologists with our collaborating neuroradiologist is more heterogeneous as some locally obtained studies may have been read by a neuroradiologist. While the local radiologists were likely mostly general radiologists, this information was not evaluated based on the study design.…”
Section: Discussionmentioning
confidence: 99%
“…7,8,[14][15][16][17][18][19][20][21][22] Most clinical studies report high specificity of CT in otosclerosis approaching 95% to 100%. 10,14,19,21,23 One cadaveric temporal bone study comparing CT and histopathologic findings of 10 temporal bones with otosclerosis and 36 controls identified three false positive cases (8%) in which connective tissue and blood vessels anterior to the oval window was falsely identified on HRCT as otospongiosis. 22…”
Section: Sensitivity Of Ctmentioning
confidence: 99%
“…Preoperative HRCTs can also be used to rule out other middle ear abnormalities, to aid in surgical planning and preoperative counseling, and to predict difficult surgeries. 3,5,8,12…”
Section: Discussionmentioning
confidence: 99%
“…2,8,10 It is helpful for institutions to have a neuroradiologist who specializes in head and neck imaging as 1 prior mentioned study showed. 8…”
Section: Discussionmentioning
confidence: 99%
“…Отбор пациентов включал данные анамнеза, традиционный осмотр ЛОР-органов, исследование слуха с помощью камертонов (пробы Вебера, Ринне, Федеричи, Желле), отомикроскопию, тональную пороговую аудиометрию, импедансомертию. С 2015 г. всем пациентам выполнялась спиральная компьютерная томография височной кости (СКТВК) с целью дифференциального диагноза с фиксацией наковальни, аномалиями развития слуховых косточек, позиции лицевого нерва, синдромом Ван-дер-Хуве, дегисценцией верхнего полукружного канала, болезнью Педжета, наличия очагов отосклероза, их локализации, распространенности и активности процесса [9,10]. Уточнение анатомо-топографических особенностей окна преддверия проводилось в соответствии с критериями, предложенными И.В.…”
Section: пациенты и методыunclassified